Peluang dan Tantangan Penerapan Paradigma Integrasi Interkoneksi Amin Abdullah dalam Studi Hukum Islam - Teguh Mulyo, Mufrod (Universitas Wahid Hasyim Semarang, 2025)
The integration-interconnection paradigm proposed by Amin Abdullah seeks to address the long-standing dichotomy between religious sciences and general sciences, which has often hindered the development of Islamic knowledge. While offering a holistic approach, the application of this paradigm within the context of Islamic law still faces resistance from conservative groups and a lack of systematic, applicable methodology. This issue has led to Islamic law often being perceived as static and unable to respond to contemporary issues such as Islamic economics, the environment, and human rights. This study aims to explore the opportunities and challenges of applying the integration-interconnection paradigm in the study of Islamic law. Using a qualitative method with a literature review approach, this research analyzes the works of Amin Abdullah and relevant secondary literature. Content analysis is employed to identify gaps in application, relevance, and strategies needed to overcome these obstacles. The results indicate that this paradigm holds significant potential for creating Islamic law that is responsive, relevant, and adaptable to the needs of the era. It successfully unites the normative aspects of religion with the historical reality of society through an interdisciplinary approach. However, conservative resistance and the lack of operational methodological guidance remain major barriers. Therefore, the development of a more inclusive applied methodology and strengthening interdisciplinary dialogue are necessary to ensure this paradigm can be optimally applied in the study of modern Islamic law